Atributos biológicos e químicos de um solo cultivado com cana-de-açúcar (Saccharum officinarum L.) fertirrigado com vinhaça - Barros, Rubens Pessoa de (2009)
The agriculture has come to pass by big changes that include the introduction of synthetic chemical products, the use of more refined machinery, the diminution of the diversification of cultures and the emergency of more specialized and large-scale producers. Consequently, in the evolution of the man and the environment relation, the environmental imbalances arose and, as result of that, there is the need of giving support to the basic cycles that guarantee the life in the land. Therefore, it is necessary to use other sources of energy which bring to itself the concept of equilibrium with the Nature, resulting in indicators of sustainability of the agroecosystems. This way, this work aimed to study the biological attributes and chemists of a soil, cultivated with sugar cane classified as Vertisoil fertirrigado with vinasse, in two agricultural areas of the São José do Pinheiro plant, in Laranjeiras, in the state of Sergipe, Brazil. One of them with fertirigation and the other one without application of vinasse. The experimental delineation was in randomized statistical blocks, with three handlings, in other words, three depths: 0-15, 15-30 and 30-45 cm, with ten repetitions. In the biological attributes, the density and diversity of the population of fungi were evaluated, it was verified that it had a significant effect of the vinasse in soil for fungi between the studied areas, mainly in the area where the vinasse is applied. The statistical analysis reveals that there was a significant difference in the populations of microorganisms between the areas A and B, which did not occur between the depths. In the chemical attributes, there was a bigger penetration of macronutrients and micronutrients in the layers 0-15 cm and 15-30 cm. The study concluded that the application of the vinasse altered the biological conditions, and the chemistry of the soil, and that the population density of the microorganisms, can be a good indicator of the quality of the soil in the areas studied, being these bioindicators of the quality of the soil. It cannot be affirmed with the information obtained, that the application of the vinasse degraded soil, preserving its quality, showing its correct and ecological use.